Suggesting a sports training program using cardio exercises to reduce fat percentage and improve body image for obese women (20-30) years - Gasmi, Abdelmalek; Cheriet, Houssem eddine (Journal of Human Sciences, 2022)
The aim of the research is to prepare a training program to develop the characteristic of quick strength for football players less than 17 years old during the competition stage and to know its impact on the development of the characteristic of quick strength. The athlete Sanawa - Mila - (5) players were used to find the coefficient of reliability and validity. As for the remaining (20) players, they were divided into two equal groups (experimental and control). And this is after conducting equivalence and homogeneity on the sample members, where the experimental group applied the proposed training program, while the control group was subjected to the trainer’s program. Training units, and then post-test and statistical treatment.